Development of Interactive Media with Using PBL to Improve Student Learning Outcomes in Grade 4th Social Science Subject - Nella Abna Tanjung; Ichwan Azhari; Sri Milfayetty (Randwick International of Education and Linguistics Science Journal, 2023)
This research would show (1) the development of interactive learning media based on problem-based learning in social studies subjects for class IV SD 112300 Kongsi sixth which has been developed suitable for use for learning, to develop interactive media based on problem-based learning in social sciences lessons in class IV SD Negeri 112300 Kongsi Enam which was developed effectively to improve the learning result. The model in this development refers to the 4-D (four-D) research and development model which consists of 4 stages namely Defining, Designing, Developing, and Disseminating. The subjects were material expert validators, media experts, language experts and twenty-five students. The data collection techniques used in the research were (1) Validation Sheet, (2) Student Learning Results Test. It used Problem Based Learning as a whole is stated to be adequate. This is proven by the validation results by material experts of 4.35 categorized as valid, media experts with 4.15 categorized as valid and language experts with 4.2 categorized as valid. The average effectiveness of interactive learning media with using PBL is 77.04% and the average effectiveness of learning using print media is 70.64%. The value of the effectiveness of interactive learning media based on problem-based learning is very suitable for use in learning and is effective in improving student learning outcomes.